No apparent cost of disease resistance on reproductive output in Acropora cervicornis genets used for active coral reef restoration in Florida - Hanna R. Koch; Yuen Azu; Yuen Azu; Erich Bartels; Erinn M. Muller (Frontiers in Marine Science, 2022)
As assisted sexual reproduction interventions continue to become embedded within coral reef restoration initiatives, it is important to understand the potential for trade-offs between key traits like reproductive output and disease resistance. Oocyte size and fecundity, quantitative measures of reproductive output and important life-history traits, can be used as proxies for coral reproductive success and health. Sexual reproduction, particularly gametogenesis, is an energetically costly process and at the physiological level, trade-offs are caused by competitive allocation of limited resources to various functions. However, resource allocation trade-offs may also have a genetic basis, and thus, different genets may differ in these aspects. Therefore, the purpose of this study was to assess the reproductive output of A. cervicornis genets with known white-band disease resistance or susceptibility by quantifying the number and size of oocytes within colonies maintained within Mote Marine Laboratory’s offshore coral spawning nursery in the Lower Florida Keys, USA. We also quantified the number of eggs and sperm packaged within gamete bundles that were collected during the August 2020 spawning event. Consistent with previous studies, we found a positive correlation between colony size and fecundity. Interestingly though, we found no evidence for a trade-off between disease resistance and reproductive output and instead found a negative correlation between disease susceptibility and oocyte size. These data are relevant for population management interventions and for managing broodstock used for active restoration where a suite of corals with different genotypes and phenotypes are continuously propagated and outplanted. Having a more comprehensive understanding of the fitness differences among candidates can help guide such efforts and ensure that a diversity of fit genets is used for restoration, which should ultimately support greater adaptive potential and population resilience.